2023
DOI: 10.1177/17562848231197509
|View full text |Cite
|
Sign up to set email alerts
|

IBD barriers across the continents: a continent-specific analysis – Australasia

Alexander T. Elford,
Rupert W. Leong,
Emma P. Halmos
et al.

Abstract: Australasia, encompassing Australia, New Zealand, and Papua New Guinea, has some of the highest prevalence’s of inflammatory bowel disease (IBD) in the world. The way IBD medicine is practiced varies between and within these countries. There are numerous shared issues of IBD care between Australia and New Zealand, whereas Papua New Guinea has its’ own unique set of circumstances. This review looks to explore some of the barriers to IBD care across the continent from the perspective of local IBD healthcare prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…5 Australasia has seen a rise in the incidence and prevalence of IBD and has one of the highest rates in the world. 6 A cross-sectional study of general practices within Australia found the estimated crude prevalence of IBD was 653 per 100,000 patients; CD: 306 per 100,0000 patients and UC: 334 per 100,000 patients. 6 and albumin levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Australasia has seen a rise in the incidence and prevalence of IBD and has one of the highest rates in the world. 6 A cross-sectional study of general practices within Australia found the estimated crude prevalence of IBD was 653 per 100,000 patients; CD: 306 per 100,0000 patients and UC: 334 per 100,000 patients. 6 and albumin levels.…”
Section: Introductionmentioning
confidence: 99%
“…6 A cross-sectional study of general practices within Australia found the estimated crude prevalence of IBD was 653 per 100,000 patients; CD: 306 per 100,0000 patients and UC: 334 per 100,000 patients. 6 and albumin levels. Operative data included history of previous surgery, duration of surgery, intraoperative complications, and additional intraoperative details.…”
Section: Introductionmentioning
confidence: 99%